2008
DOI: 10.1007/s11010-008-9723-7
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial ischemia and reperfusion injury in rats: lysosomal hydrolases and matrix metalloproteinases mediated cellular damage

Abstract: The aim of this study was to evaluate the time course events of cellular damage during myocardial ischemia and reperfusion injury in rats and to find out a correlation between the structural alterations with respect to the biochemical changes. Cardiac biomarkers and lysosomal enzymes viz. cathepsin D, acid phosphatase and beta-glucuronidase and matrix metalloproteinases (MMPs) were evaluated at different time points, in response to ischemia-reperfusion induced oxidative stress in an isolated rat heart model pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…VAMP7-syntaxin4-SNAP23 participates in synaptotagmin VII-regulated lysosomal exocytosis in fibroblasts (23). VAMP8-syntaxin4-SNAP23 is involved in cytokine/chemokine trafficking by segregating lysosomal secretory granules in mast cells (24). These four different ternary SNARE complexes allowed us to test if NSF-driven disassembly is influenced by primary sequence variation of the SNARE core domains and by differences in the N-terminal domains ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…VAMP7-syntaxin4-SNAP23 participates in synaptotagmin VII-regulated lysosomal exocytosis in fibroblasts (23). VAMP8-syntaxin4-SNAP23 is involved in cytokine/chemokine trafficking by segregating lysosomal secretory granules in mast cells (24). These four different ternary SNARE complexes allowed us to test if NSF-driven disassembly is influenced by primary sequence variation of the SNARE core domains and by differences in the N-terminal domains ( i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Cytokines and reactive oxygen species mobilize acid hydrolases, which damage myofibrillar proteins, leading to increases in infarct size and eventually to apoptosis or necrosis of the heart tissue . Phloroglucinol treatment significantly reduced oxidative stress by elevating antioxidant enzyme levels, which might be a possible cause of the reduction of infarct size in treated diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Serum total CK activity and CK-MB concentration rise in parallel following myocardial injury. A significant elevation in the level of CK-MB has been observed in the heart effluent during myocardial ischemia band reperfusion in isolated rat hearts [32]. Jaffe et al, (2000) also reported that serum CK-MB is considerably more specific for myocardial damage [33].…”
Section: Discussionmentioning
confidence: 97%